Parametric modelling of wavy-finned flattened tube performance for application in air-cooled heat exchanger optimization - Van der Spuy, Sybrand Johannes (Stellenbosch : Stellenbosch University, 2025)
van der Spuy, S. J. 2025. Parametric Modelling of Wavy-Finned Flattened Tube Performance for Application in Air-Cooled Heat Exchanger Optimization. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5572518f-6974-4fcc-b85c-36b50b4c19ff